The impact of cohabitation and divorce on partners' labour force participation: comparing Britain with Flanders - Joris Ghysels (University of Essex, Institute for Social and Economic Research (ISER), 2000)
In this paper we look into the possible impact on labour force participation of two demographic variables that have undergone considerable changes in the past few decades: divorce and cohabitation. More specifically we analyse the labour force participation probabilities of men and women currently living with a partner and study the impact of a previous divorce or separation and current non-marital cohabitation. We use seven waves of data of the BHPS and the PSBH to compare British results with results of Flemish individuals. Estmates suggest that cohabitation implies significantly higher labour force participation for women, especially for the older cohorts. A divorce experience is generally found to be insignificant, except for British men who are less likely to be in the labour force after experiencing a divorce or separation than without this experience.
Keywords: 330